Coendemicidade entre hanseníase e leishmaniose tegumentar no estado de Mato Grosso, Brasil - Carvalho, Amanda Gabriela de (2022)
Leprosy and tegumentary leishmaniasis (TL) are skin-related neglected tropical diseases highly endemic in the Brazilian state of Mato Grosso. Although leprosy and TL share many epidemiological and clinical features, few studies have addressed the coendemicity between them. This study analyzed epidemiological and clinical aspects related to the coendemicity between leprosy and TL in Mato Grosso. All new cases of leprosy and TL reported between 2008 and 2017 in the Brazilian Notifiable Diseases Information System were included. An ecological study was conducted to verify the spatial distribution and spatial clusters for leprosy and TL at the municipality level. Spatial analyzes were performed using the global empirical Bayesian estimator, Moran's global (I) and local indexes and scan statistics. Furthermore, the sociodemographic profile of leprosy and TL cases were described. In sequence, a retrospective cohort study was conducted (i) to identify cases diagnosed with both leprosy and TL, (ii) to estimate the probability of the diagnosis of leprosy or TL among individuals with a previous diagnosis of one of these diseases, and (iii) to investigate the demographic factors associated with the time elapsed between the diagnosis of both diseases. For that, a probabilistic linkage procedure, survival analysis, and Cox proportional hazards modeling were employed. A spatial characterization of the cases diagnosed with both diseases were also performed. Moreover, the clinical characteristics of leprosy and TL were compared between cases diagnosed with both diseases and those diagnosed with leprosy or TL using a chi-square test followed by multivariate logistic regression. Both leprosy (n=28,204) and TL (n=24,771) occurred at hyperendemic levels with spatial heterogeneity. An extensive overlap of high-risk clusters for leprosy (RR=2.0; p<0.001) and TL (RR=4.0; p<0.001) in the municipalities located in the north and northeast mesoregions was observed. Moran's global analyses revealed a spatial autocorrelation for leprosy (I=0.228; p=0.001) and TL (I=0.311; p=0.001) and a correlation between them (I=0.164; p=0.001). Both diseases prevailed in urban areas, among male individuals, aged between 31-60 years, of mixed race, and with low level of schooling. A total of 414 patients were diagnosed with leprosy and TL, mainly in the municipalities of the north and northeast mesoregions. The probability of an individual being diagnosed with both diseases increased over time, from 0.2% in the first year to 1.0% within seven years. Male sex (HR=2.3; 95%CI=1.7–2.9) and low level of schooling (HR=1.5; 95%CI=1.2–1.9) were positively associated with the time elapsed between the diagnosis of both diseases. The risk of the diagnosis of both diseases was higher among individuals aged 40-55 years. Cases diagnosed with both leprosy and TL presented higher odds of having nerve damage (OR=1.34; 95%CI=1.09–1.66) and leprosy reactions (OR=1.35; 95%CI=1.04–1.76) than those diagnosed only with leprosy. Mucocutaneous leishmaniasis (OR=2.29; 95%CI=1.74–3.00) was more frequent among individuals with both diagnoses when compared to those who only had TL. These results may contribute to a better understanding of the coendemicity between leprosy and LT and, consequently, to an improvement in the diagnosis, treatment, and possible integrated control of these diseases in endemic areas.